2002
DOI: 10.1183/09031936.02.00257902
|View full text |Cite
|
Sign up to set email alerts
|

Iodixanol inhibits exogenous surfactant therapy in rats with acute respiratory distress syndrome

Abstract: Optimal alveolar distribution of exogenous surfactant is an important determinant of its beneficial effect. This distribution can be determined by suspending surfactant in a radiological contrast medium before intratracheal instillation, followed by radiological imaging. Iodixanol is reported to be a safe contrast medium that causes no lung injury when instilled intratracheally.In this study, the effects of surfactant suspended in saline were compared with surfactant suspended either in 4:1 saline-iodixanol (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It is also time‐dependent and variable, depending on the type of contrast medium used. Based on previous findings the concentrations of the different contrast media used in the present study were 60–70 mg iodine ml −1 (Kesecioglu et al. , 2002).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is also time‐dependent and variable, depending on the type of contrast medium used. Based on previous findings the concentrations of the different contrast media used in the present study were 60–70 mg iodine ml −1 (Kesecioglu et al. , 2002).…”
Section: Discussionmentioning
confidence: 85%
“…However, there are no data on the effect of contrast media when instilled or accidentally ingested into lungs with acute respiratory distress syndrome (ARDS). In an ARDS model in rats which is always associated with capillary leakage in the lungs, it has been recently demonstrated that exogenous surfactant dissolved in 160 mg iodine ml −1 Visipaque ® (iodixanol) resulted in an increase of surface tension, which in turn inhibited the exogenous surfactant activity (Kesecioglu et al. , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the true external diameter was about 1.2 nm. The nanotubes were in a suspension of 0.15 mg/mL with 1% mass/volume sodium deoxycholate surfactant (SDC) (24 mM) and 6-7% mass/volume iodixanol salt (IS) [27]. The lengths were measured in the SEM as previously described to be 83 ± 26 nm.…”
Section: Type-ii Suspensionmentioning
confidence: 99%